Association of parents' nutritional status, and sociodemographic and dietary factors with overweight/obesity in schoolchildren 7 to 14 years old - Bernardo,Carla de Oliveira (2012)
To assess the association of parents' nutritional status, and dietary and sociodemographic factors with overweight/obesity in schoolchildren in Florianópolis Island, Santa Catarina State, Brazil, this cross-sectional epidemiological study examined 2,826 schoolchildren 7 to 14 years old, classified according to body mass index curves for age and sex recommended by the International Obesity Task Force. Data were analyzed using Poisson regression. The final model showed overweight/obesity in boys associated directly with father's educational level, mother's age, and parents' nutritional status, and inversely with mother's educational level, and number of daily meals. Among girls, it associated directly with parents' nutritional status and the schoolchildren's age, and inversely with consumption of risk foods. The variables that associated with overweight/obesity differed between the sexes, except parents' nutritional status. Boys and girls with both parents overweight or obese were, respectively, 80% and 150% more likely to exhibit the same diagnosis, indicating the need for interventions that include the family environment.